2022
DOI: 10.3389/fanim.2022.883940
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Resilience Parameters Following LPS Injection Based on Activity Measured With Computer Vision

Abstract: Resilience could be referred to as the animal’s ability to successfully adapt to a challenge. This is typically displayed by a quick return to initial metabolic or activity levels and behaviors. Pigs have distinct diurnal activity patterns. Deviations from these patterns could potentially be utilized to quantify resilience. However, human observations of activity are labor intensive and not feasible in practice on a large scale. In this study, we show the use of a computer vision tracking algorithm to quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The same animals were used as described in Parois et al (2022a) and van der Zande et al (2022).To summarize, a total of 144 Tempo × Topigs-20 pigs (n = 71 females; n = 73 males) were used during the experiment, spread over three batches (n = 48 pigs per batch). During lactation, half of the sows and their piglets were housed in a conventional farrowing pen (CONV) (mean ± SD; sow parity = 4.2 ± 1.8) and the other half in an alternative group housing system (AHS) (parity = 4.0 ± 1.7) at the Swine Innovation Centre (Sterksel, the Netherlands).…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations
“…The same animals were used as described in Parois et al (2022a) and van der Zande et al (2022).To summarize, a total of 144 Tempo × Topigs-20 pigs (n = 71 females; n = 73 males) were used during the experiment, spread over three batches (n = 48 pigs per batch). During lactation, half of the sows and their piglets were housed in a conventional farrowing pen (CONV) (mean ± SD; sow parity = 4.2 ± 1.8) and the other half in an alternative group housing system (AHS) (parity = 4.0 ± 1.7) at the Swine Innovation Centre (Sterksel, the Netherlands).…”
Section: Animalsmentioning
confidence: 99%
“…At the other extreme, boredom or negative affective states in barren housed pigs, induced by limited possibilities to show important behaviours, may cause lethargic behaviour (see Bolhuis et al, 2005;Fureix and Meagher, 2015;Luo et al, 2020b). Van der Zande et al, (2022) indeed showed lower activity of barren housed pigs as compared with those in enriched housing. The stress, restlessness or negative affective states that potentially underly the high variation in activity in barren housed pigs, might then exacerbate the cortisol response to LPS.…”
Section: Baseline Activity and Physiological Response To Lpsmentioning
confidence: 99%
See 2 more Smart Citations